A Single Case Evaluation of an Emotion Regulation Training in Adolescents - Elisa Boelens; Laura Wante; Leentje Vervoort; Sandra Verbeken; Lien Goossens; Caroline Braet (Psychologica Belgica)
The high prevalence of mental health problems, especially in adolescence, promotes research on psychological interventions. Recently, focus has shifted from disorder specific to transdiagnostic interventions. Since emotion regulation (ER) underlies various mental disorders, targeting this transdiagnostic mechanism is Particulary interesting. The current study aimed to investigate the feasibility and effectiveness of an emotion regulation training for children and adolescents (EuREKA) in six adolescents (M = 12.50, SD = 1.52; 50% girls) enrolled in an inpatient treatment center for internalizing and/or externalizing problems. Using a single case design, ER was monitored weekly during both baseline and treatment phase. In addition, pretraining and posttraining measurements on both psychopathology and ER were included. Although caution is warranted due to the nature of the study and the small sample size, the overall results suggest that EuREKA is a feasible and potentially promising approach for treating both internalizing and externalizing problems. However, some mixed results in the individual outcomes were observed, making it challenging to provide general conclusions on the effectiveness of EuREKA.